An Interdisciplinary Team Approach for the Severely Handicapped Individulas Living with their Families - MIYOSHI Takahiko; SUMIDA Mariko; NAKAGAWA Hiroyuki; MIYOSHI Naomi; INABA Yuko; OHTSUKA Katsuhiro; SANO Nozomi; MATSUMOTO Shuhei; KUZUME Kazuyo; NAGAO Hideo (Japanese Journal of National Medical Services, 1994)
Outpatient clinic program for the severely handicapped individuals living at home was started in April, 1991 at our hospital. Fourteen individuals, age between 2 and 24 years have continued to participate in this program. The purpose of this outpatient clinic program was to assess and accept ea h individual as they were, and their family dynamics. Furthermore, the main purpose was to encourage what each patient was able to do and enjoyed. This resulted in inducing more positive views and attitudes from the parents. The parents showed more interest to their handicapped children and more interactions between the parents and children were seen. The intervention of this outpatient clinic program was a success in this respect, but further follow-up is needed. 在宅重症心身障害児・者(在宅児)の援護を目的として, 平成3年4月より「外来相談」を実施した. 対象は継続的に参加できた14例, 年齢は4歳から24歳であった. 「外来相談」の指導方針では患者・家族の現状, 実態をすべてあるがままに受けとめ, 患者の喜ぶこと, できることをさがして発展させることを最大の目標とした. その結果, 「外来相談」を一つのきっかけとして, 療育に対する親の姿勢が積極的となり, 患者が変わり, そのことが親や周囲の人をさらに刺激してかかわりが増えるというよい循環が成立した. したがって, この指導方針は妥当なものであったと考えられ, さらに長期的検討をしてゆきたい.